The psychometric properties of the Portuguese version of the State Mindfulness Scale - Andrade, C.; Arriaga, P.; Carvalho, M. (Mindfulness, 2019)
Objectives: This study examined the psychometric properties of the State Mindfulness Scale (SMS) in a sample of the Portuguese population. Methods: To test the validity and reliability of SMS, a survey was administered to 287 participants (236 women; aged between 18-71 years old) with and without previous mindfulness practice. Two weeks after the first assessment, 41 participants were evaluated to test the stability of the SMS. Results: Consistent with contemporary psychological models of mindfulness, the confirmatory factor analyses supported a hierarchical structure entailing one second-order state mindfulness factor and two first-order factors: one related to body sensations and the other reflecting mental events. The two first-order dimensions of state mindfulness correlated positively with the dimensions of Observe, Nonreactivity, and Describe of the dispositional mindfulness scale. The SMS global scores were independent of emotional suppression and cognitive reappraisal, and of social desirability. The SMS showed acceptable internal and test-retest reliability. Conclusions: Overall, the Portuguese version of the scale has acceptable psychometric qualities and can be used to measure mindfulness states, regardless of previous mindfulness practice.